2020
DOI: 10.1136/jitc-2020-000809
|View full text |Cite
|
Sign up to set email alerts
|

In situ vaccination at a peripheral tumor site augments response against melanoma brain metastases

Abstract: BackgroundImmune checkpoint inhibition (ICI) alone is not efficacious for a large number of patients with melanoma brain metastases. We previously established an in situ vaccination (ISV) regimen combining radiation and immunocytokine to enhance response to ICIs. Here, we tested whether ISV inhibits the development of brain metastases in a murine melanoma model.MethodsB78 (GD2+) melanoma ‘primary’ tumors were engrafted on the right flank of C57BL/6 mice. After 3–4 weeks, primary tumors were treated with ISV (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(26 citation statements)
references
References 52 publications
2
24
0
Order By: Relevance
“…We are now evaluating this treatment approach in patients with metastatic melanoma in a phase I/ II trial (NCT03958383). Although this ISV regimen consistently results in a potent systemic anti-tumor immune response in mice leading to complete response at distant tumor sites that are not directly treated with radiation or intratumoral injection (12), we recently reported that this treatment is much less effective in controlling tumor that is present in the brain at time of treatment (13). This is consistent with prior studies demonstrating the restrictive effects of the brain tumor microenvironment on anti-tumor immunity (14)(15)(16)(17)(18)(19).…”
Section: Introductionsupporting
confidence: 87%
See 3 more Smart Citations
“…We are now evaluating this treatment approach in patients with metastatic melanoma in a phase I/ II trial (NCT03958383). Although this ISV regimen consistently results in a potent systemic anti-tumor immune response in mice leading to complete response at distant tumor sites that are not directly treated with radiation or intratumoral injection (12), we recently reported that this treatment is much less effective in controlling tumor that is present in the brain at time of treatment (13). This is consistent with prior studies demonstrating the restrictive effects of the brain tumor microenvironment on anti-tumor immunity (14)(15)(16)(17)(18)(19).…”
Section: Introductionsupporting
confidence: 87%
“…C57BL/6-Tg (Foxp3 DTR/EGFP) 23.2 Spar/Mmjax ''DEREG'' mice were purchased from the Jackson Laboratory (MMRRC; Bar Harbor, ME). Treg depletion with diphtheria toxin was achieved following a prior methodology, as reported elsewhere (13,27,30) by daily intraperitoneal (i.p.) injection of 1 lg diphtheria toxin (MilliporeSigma, St. Louis, MO) diluted in PBS for 2 days at day 14 and 15 postirradiation, to ensure presence of melanoma brain tumor prior to Treg depletion.…”
Section: Murine Tumor Modelsmentioning
confidence: 99%
See 2 more Smart Citations
“…This reaction was dependent on ADCC and T cell infiltration, and it conferred protection against rechallenge. Even greater anti-tumor responses were seen when radiation, immunocytokine, and anti-CTLA-4 blockade were combined in immunocytokine antigen-positive tumors [ 156 , 157 ]. However, the presence of a secondary untreated tumor negatively impacted the immunocytokine/radiation efficacy in primary treated pancreatic and melanoma tumors.…”
Section: Immunocytokines In Combination Therapeutic Approachesmentioning
confidence: 99%